2020
DOI: 10.1186/s12940-020-00582-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of haematological malignancies in residents living near petrochemical facilities

Abstract: Background:The petrochemical industry is a major source of hazardous and toxic air pollutants that are recognised to have mutagenic and carcinogenic properties. A wealth of occupational epidemiology literature exists around the petrochemical industry, with adverse haematological effects identified in employees exposed to 'low' concentrations of aromatic hydrocarbons (benzene, toluene, ethylbenzene, and xylene). Releases from the petrochemical industry are also thought to increase the risk of cancer incidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 63 publications
0
22
0
2
Order By: Relevance
“…Their results showed elevated meta-relative risks of mesothelioma, malignant skin melanoma, and acute lymphoid leukemia and no elevated risks of total leukemia, acute non-lymphocytic leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, multiple myeloma, non-Hodgkin’s lymphoma (NHL), and lung and kidney cancers. The most recent review of residents near petroleum industry sites has also found elevated risks for leukemia (the review only focused on hematological malignancy) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed elevated meta-relative risks of mesothelioma, malignant skin melanoma, and acute lymphoid leukemia and no elevated risks of total leukemia, acute non-lymphocytic leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, multiple myeloma, non-Hodgkin’s lymphoma (NHL), and lung and kidney cancers. The most recent review of residents near petroleum industry sites has also found elevated risks for leukemia (the review only focused on hematological malignancy) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review recognized 16 reports, which jointly evaluated the occurrence of hematological malignancies across 187,585 residents residing close to a refinery. Inhabitants from the areas less than 5 km from a petrochemical facility presented a 30% higher risk of developing hematological malignancies than habitants from areas with no petrochemical activity [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its carcinogenicity, specifically in relation to its chronic exposure, quantitative changes in blood cells are reported, such as leukopenia, thrombocytopenia, and erythropenia, and, among the most serious effects, acute and chronic leukemias 14 . A systematic review with meta-analysis conducted by Jephcote et al 15 evaluated residents who lived near petrochemical centers and recorded a higher incidence of hematologic neoplasia in relation to the general population. In Brazil, the Brazilian National Cancer Institute (INCA), together with the Ministry of Health, developed a manual on cancer surveillance related to work and the environment, relating, among other chemical substances, benzene as the main cause of leukemia among workers in the petrochemical sector, including those who distributed and traded fossil fuels, especially petrol 16 .…”
Section: Discussionmentioning
confidence: 99%